MEKANISME ASURANSI BERBASIS KEUANGAN SYARIAH - Syuhada, Erwin Febrian; Mursyid, Mursyid (Ekonomi Syariah STAI Sangatta Kutai Timur, 2024)
This research discusses Sharia finance-based insurance mechanisms as an alternative that complies with Sharia principles in the financial industry. The conventional insurance often involves elements of usury and speculation, which are contrary to Islamic law. In this context, Sharia finance-based insurance mechanisms offer an approach that is in line with Islamic financial principles. Sharia insurance emphasizes the concept of cooperation and mutual assistance between participants. This mechanism includes establishing a community fund, which is used to assist its members in dealing with certain risks. In addition, the principles of mudharabah and musyarakah are applied to manage these funds fairly and transparently. This research uses literature analysis methods to investigate the main concepts in Sharia finance-based insurance. The analysis results show that a Sharia finance-based insurance mechanism can be a choice that is more in line with Islamic values while providing significant economic benefits. Thus, this research contributes to understanding the importance of developing financial products that comply with Islamic financial principles to promote financial inclusion and sustainable development.